Genetic Background Influences the Propagation of Tau Pathology in Transgenic Rodent Models of Tauopathy - Smolek, Tomas; Cubinkova, Veronika; Brezovakova, Veronika; Valachova, Bernadeta; Szalay, Peter; Zilka, Norbert; Jadhav, Santosh (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD), the most common tauopathy, is age dependent progressive neurodegenerative disease. Epidemiological studies implicate the role of genetic background in onset and progression of AD. Despite mutations in familial AD, conundrums of risk factors have been implicated in sporadic AD, of which the onset is unknown. In AD, there is a sequential and hierarchical spread of tau pathology to other brain areas. Studies have strived to understand the factors that influence this characteristic spread. Using transgenic rat models with different genetic background, we reported that genetic background may influence the manifestation of neurofibrillary pathology. In this study we investigated if genetic background has an influence in the spread of tau pathology using hippocampal inoculations of insoluble tau from AD brain in rodent models of tauopathy with either spontaneously hypertensive (SHR72) or Wistar-Kyoto (WKY72) genetic background. We observed that insoluble tau from human AD induced AT8 positive neurofibrillary structures in the hippocampus of both lines. However, there was no significant difference in the amount of the neurofibrillary structures, but the extent of spread was prominent in the W72 line. On the other hand, we observed significantly higher levels of AT8 positive structures in the parietal and frontal cortical areas in W72 when compared to SHR72. Interestingly, we also observed that the microglia in these brain areas in W72 were predominantly phagocytic in morphology (62.4% in parietal and 47.3% in frontal), while in SHR72, the microglia were either reactive or ramified (67.2% in parietal and 84.7% in frontal). The microglia in hippocampus and occipital cortex in both lines were reactive or ramified structures. Factors such as gender or age are not responsible for the differences observed in these animals. Put together, our results, for the first time, show that immune response modulating genetic variability is one of the factors that influence the propagation to tau neurofibrillary pathology.